STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA SETEMPAT BATU GALEH DI KENAGARIAN SUNGAI ANTUAN KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Insani, Fanila; Juita, Novia; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2018)
The aims of this research are (a) to describe the structure of folklore of local legend Batu Galeh in Kenagarian Sungai Antuan Mungka, district Lima Puluh Kota. (b) todescribe the social function of folklore of local legend namely Batu Galeh in Kenagarian Sungai Antuan, Mungka Sub-district, Lima Puluh Kota. This research type is qualitative research with descriptive method. Data of this research is local folklore legend of Batu Galeh. The data technique collection is done in two stages. The first stage, the stage of recording the folklore of local legend Batu Galeh and then the result of recording is transcribed. Next, transcription results will be translated from local language Minangkabau in Kenagarian Sungai Antuan Mungka district Lima Puluh Kota into Indonesian language. The second stage, collecting data about the enviroment story. The result of this research is found that in the folklore of local legend Batu Galeh has 2 characters, advanced groove, and background of place of kampung, rantau, and place of rest, background of time happened in ancient time and some atmosphere background that is happy, sad, sorry. The social functions found are identity, education, social control and group identity.Keywords: Structure, Social Function, Batu Galeh